Development of Multimedia-Based Teaching Materials in Mastering Linguistic Aspects - Darwin, David; Muliastuti, Liliana; Setiadi, Syamsi; Anwar, Miftahulkhairah (Universitas Negeri Semarang, 2021)
The use of learning multimedia has numerous advantages, including accommodating variances in student learning styles, allowing students to choose the content to be studied, and allowing students to change their learning speed by selecting particular buttons given in multimedia learning. This study aims to investigate the development of multimedia-based teaching materials in the mastery of linguistic aspects of the understanding of listening to Mandarin. This research method in the form of literature review was conducted based on issues, methodologies, equations and further research proposals. The findings revealed that the understanding of listening to their language after the application of materials that indicate multimedia had an influence on the development of mandarin teaching material materials.So it can be concluded that, multimedia is one of the important tools in teaching understanding listening to mandarin. With the right elements and the right storyboard can help motivate students and improve listening skills.